Faster and Stronger: The Role of Anaerobic Exercises in Swimming Performances - Rangaraj, K.; Sakthivel, S. (Journal of Neonatal Surgery, 2025)
The purpose of the research was to investigate how anaerobic exercise affected particular physiological and physical characteristics. A total of 40 male swimmers from Chennai district, aged between 17 and 21 years, were randomly selected as participants. The study took into account a number of characteristics, including resting heart rate, endurance of muscles, cardio-respiratory endurance, aerobic workouts (an uncontrolled variable), and vital capability. The research employed a pre-test and post-test randomized group design. Participants were randomly divided into two equal groups: Group I, consisting of 20 participants, underwent anaerobic training five days a week for eight weeks, while Group II, also comprising 20 participants, served as the control group and did not engage in anaerobic training. Post-tests were administered following eight weeks of training, while pre-tests were administered before to the training session in order to gather data. For the chosen physiological variables, the pre-test and post-test means of the control and experimenter groups were compared using descriptive analysis and Analysis of Covariance (ANCOVA). The analysis's significance threshold was set at 0.05. The experimental group's resting heart rate, vital capacity, muscular endurance, and cardio-respiratory endurance were significantly improved after the training, according to the results. Conversely, no significant differences were observed in the control group for these variables. Based on these results, it was concluded that anaerobic training significantly enhances selected physical and physiological parameters